RETRACTED: Study results of soil properties and calculation of stability of the Almaluu-Bulak landslide slope - Jamanbaev Murataly; Omuraliev Sagyndyk; Umarov Talantbek; Falaleev Gennady (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001